Review of cancer cell resistance mechanisms to apoptosis and actual targeted therapies. Issue 11 (17th November 2021) - Kulbay, Merve; Paimboeuf, Adeline; Ozdemir, Derman; Bernier, Jacques
Abstract: The apoptosis pathway is a programmed cell death mechanism that is crucial for cellular and tissue homeostasis and organ development. There are three major caspase‐dependent pathways of apoptosis that ultimately lead to DNA fragmentation. Cancerous cells are known to highly regulate the apoptotic pathway and its role in cancer hallmark acquisition has been discussed over the past decades. Numerous mutations in cancer cell types have been reported to be implicated in chemoresistance and treatment outcome. In this review, we summarize the mutations of the caspase‐dependant apoptotic pathways that are the source of cancer development and the targeted therapies currently available or in trial.